Candida albicans induces TLR2/MyD88/NF-κB signaling and inflammation in oral lichen planus-derived keratinocytes - Jianwei Liu; Fanghui Geng; Hongying Sun; Xiaxia Wang; Hui Zhang; Qiaozhen Yang; Jie Zhang (Journal of Infection in Developing Countries)
Introduction: The risk of oral lichen planus (OLP), a chronic inflammatory oral mucosal disease, becoming malignant increases by 21-fold in patients with fungal infection. This study examined the impact of Candida albicans exposure on Toll-like receptor (TLR) signaling in primary keratinocyte cultures obtained from OLP patients.